Reliability assessment of pulsed thermography and ultrasonic testing for impact damage of CFRP panels. (March 2019) - Duan, Yuxia; Zhang, Hai; Maldague, Xavier P.V.; Ibarra-Castanedo, Clemente; Servais, Pierre; Genest, Marc; Sfarra, Stefano; Meng, Jianqiao
Abstract: In order to quantitatively compare the reliability of pulsed thermography and ultrasonic testing techniques, a set of thirty-five Carbon Fiber Reinforced Plastic (CFRP) composite panels with impact damages are inspected by pulsed thermography and ultrasonic C-scan. The comparative experimental results and Probability of Detection (PoD) analysis results are presented. The quantitative comparison shows that pulsed thermography testing has smaller defect size at 90% PoD with 95% confidence level, i.e. a 90/95 values than ultrasonic testing for the parameters and setup used in the inspections of these thirty-five CFRP composite panels.